All Days 2010
DOI: 10.2118/128067-ms
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Pseudocrosslinked Micellar Fluids: Optimal Solution for Fluid-Loss Control With Internal Breaking

Abstract: Micellar fluids with viscoelastic behavior, or viscoelastic surfactant fluids, are used in the oil industry as completion and stimulation fluids. The viscoelastic (i.e. viscous and elastic) behavior of these fluids is based on the overlap and entanglement of very long worm-like-micelles. High fluid leak-off has, however, limited their application for hydraulic fracturing and frac-packing applications. Recent developments have found that micellar fluids can have wall-building leak-off control similar to crossli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 13 publications
0
34
0
Order By: Relevance
“…Therefore, it is reasonable to speculate that a proper additive should also have great effects on the erosion characteristics of a SC-CO2 jet. Moreover, nano-silica is an appropriate kind of additive for improving the filtration properties of drilling fluid and enhancing the well bore stability, especially under high temperature and pressure conditions [30][31][32][33]. Also, Li et al experimentally investigated the effect of CO2 fracturing, influenced by a nano-silica additive, and concluded that the effect of nano-silica causes a decrease in CO2 fingering and an increase in the drainage area.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is reasonable to speculate that a proper additive should also have great effects on the erosion characteristics of a SC-CO2 jet. Moreover, nano-silica is an appropriate kind of additive for improving the filtration properties of drilling fluid and enhancing the well bore stability, especially under high temperature and pressure conditions [30][31][32][33]. Also, Li et al experimentally investigated the effect of CO2 fracturing, influenced by a nano-silica additive, and concluded that the effect of nano-silica causes a decrease in CO2 fingering and an increase in the drainage area.…”
Section: Introductionmentioning
confidence: 99%
“…Advances such as internal breakers and pseudo crosslinkers coupled with the low molecular weight of VES have led to fluids that can simultaneously control leak-off, maintain high viscosity, and controllably break and reduce viscosity in order to flow back the fluid. In a further development, fluid loss in pseudo-crosslinked systems can be further reduced by adding 0.2 to 10 vol% mineral oil (Huang and Crews 2009b;Huang et al 2010a). The oil droplets collected in the filter cake over time along with the nanoparticles and micelles, and the fluid loss continued to improve.…”
Section: Spe-173776-msmentioning
confidence: 99%
“…The formation of micelle-nanoparticle junctions acts as physical cross-links between micelles and these junctions help to have significant viscosity and elasticity in dilute and semidilute wormlike micelles. Huang et al (2010) measured the viscous and elastic moduli of conventional and nanoparticle pseudocrosslinked wormlike micelles in brine. The rheological data shows that the addition of nanoparticles increased the surfactant micellar fluid's zero shear rate viscosity more than 100 times.…”
Section: Introductionmentioning
confidence: 99%